Vertical extension of a multi-storey reinforced concrete building - Bahrami, Alireza; Deniz, Suleyman; Moalin, Hassan (Zielona Góra: Uniwersytet Zielonogórski)
The global population is increasing annually; thus, there is a need for more housing and buildings worldwide. As cities grow outward and buildable lands become scarce, it is necessary to increase the height of existing buildings in cities, especially where the height of the buildings is low. For crowded cities, the storey extension is an increasingly popular measure that can meet market demand for centrally located houses.
Keywords: vertical extension; reinforced concrete building; utilisation ratio; reaction force; deflection